GERAKAN FEMINISME ISLAM DALAM PERSPEKTIF FATIMAH MERNISSI - Widyastini, Widyastini (Jurnal Filsafat "WISDOM", 2008)
AbstractThe purpose of this research is to know the women’s role inthe scope of social life, nation and country. The varieties ofunjustness to women happened in every part of this world. They are considered as a weak creature, so that oppression always happened to them. They should act bravely to face those abuses by themselves. As God creatures, men and women have the same status before Allah SWT. Instead of their advantages and disadvantages, they should cooperate and help each other for welfare and peaceful society.The frequently of unjustness conduct or abuse toward women is a reason why a women movement appeared which was pioneered by Fatimah Mernissi. This movement aimed to break the old fashioned tradition society which is not appropriate with the recent world, namely Islamic feminism movement. It is an Islamic Women movement which try to get the same conduct betwen women and men in the boundary of Islam tenet.Based on the result of the analyzed research a conclusion can be drawn: Fatimah Mernissi’s Islamic Feminism Movementcontradicted with Islam tenets either in Ijtihad, As Sunnah and Holy Koran.Keywords: Fatimah Mernissi, Islamic feminism movement